Kinerja Dinas Kependudukan dan Pencatatan Sipil Kabupaten Klungkung berdasarkan Metode Balance Scorecard - Prabandari, Komang Ayu Triska; Asri Dwija Putri, I Gusti Ayu Made (E-Jurnal Akuntansi, 2019)
The purpose of this research to assess the performance of the Disdukcapil Klungkung using four prescriptive balance scorecard. This research used data from the government agency performance report (LKjIP) and the dissemination of questionnaires. The data analysis techniques in research in using descriptive analysis by analyzing the data of the four-perspective balance scorecard. The results of this study show results of financial performance based on value for money categorized reasonably well. The performance of the customer is assessed by the customers satisfaction index categorized as well because the community is satisfied with the service provided. The performance of the internal process is assessed by Service Cycle Efficiency (SCE) and the perspective of growth and learning assessed by the employee's productivity ratio is good . Keywords : Performance; Balance Scorecard; Prespective; Value For Money